A Study on the Psychological Capital and Stress Coping Strategy of Competition on Sports Performance for Table Tennis Player of High School Student (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
A Study on the Psychological Capital and Stress Coping Strategy of Competition on Sports Performance for Table Tennis Player of High School Student